High-dose fotemustine in temozolomide-pretreated glioblastoma multiforme patients: A phase I/II trial. Issue 27 (July 2018) - Marinelli, Alfredo; Lamberti, Giuseppe; Cerbone, Luigi; Cordua, Nadia; Buonerba, Carlo; Peluso, Gianfranco; Di Lorenzo, Giuseppe; De Placido, Sabino
Abstract: Background: Glioblastoma multiforme (GBM) is a rare and deadly disease, with a reported average incidence rate of 3.19 cases per 100, 000 inhabitants. Fotemustine, a third-generation nitrosourea with an alanine phosphor carrier that facilitates cellular penetration, has been extensively investigated in the setting of recurrent/progressive disease after initial treatment. Fotemustine is usually administered following a schedule consisting of 3 doses every week, followed by maintenance doses administered every 3 weeks. Methods: In this phase I/II trial, we aimed to assess whether the use of a biweekly regimen allowed administration of higher dose than the standard 100 mg/m 2 dose approved per label indication in a population of patients with recurrent GBM. In this phase I/II trial, fotemustine was administered intravenously over 1 hour every 2 weeks at either 120 or 140 mg/m 2 doses for up to 1 year, until disease progression, unacceptable toxicity, or patient's request to withdraw from the study. The phase I part of the trial was conducted following the classic 3+3 study design. The phase II part of the trial was a single-arm study. The primary efficacy endpoint was the percentage of patients who had not progressed after 24 weeks (PFS-24). Results: Thirty-seven patients were enrolled in this phase I/II trial from August 2006 to November 2011. Treatment was well tolerated in the overall population. Main severe toxicity was grades 3 and 4 thrombocytopenia, which occurred in 4 of 6 patients treated at the 140 mg/m 2 dose level and in 3 of 31 patients treated at 120 mg/m 2 . Median PFS and overall survival were 12.1 (1–40.2) weeks and 19.7 (1–102) weeks, respectively. Conclusion: We conclude that fotemustine can be safely administered at 120 mg/m 2 biweekly. The efficacy of such modified schedule and doses should be compared to the biweekly schedule at 80 mg 2 and the standard weekly schedule at 80 to 100 mg/m 2 .